Ecolabeling for Green Economic Development in the Buffer Zones and Transition Areas of the World Biosphere Reserves in Vietnam - Van Dinh, Ha; Thinh, Nguyen An; Anh, Le Ngoc (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
Ecolabeling of a biosphere reserve refers to the use of the logo of a biosphere reserve associated with ecological, environmental, and other conditions (criteria) which are assigned to a product or a service so as to meet certain requirements. The value of an ecolabel is considered as the value of the ecological environment, and the biodiversity of a biosphere reserve. This paper provides a theoretical basis for a green-growth, ecolabel i.e.: Builds green economy orientations in the buffer zones and transition areas of biosphere reserves on the basis of adhering to the goals and orientations of the National Strategy for Green Growth; Proposes an ecolabeling condition framework/criteria to promote a green economy in the buffer zones and transition areas of the biosphere reserve in meeting Vietnam’s and UNESCO’s sustainable development policy on green growth in biosphere reserves that are recognized by UNESCO.